Security, identity, and interests : a sociology of international relations - McSweeney, Bill (Cambridge studies in international relations, 1999)
In this book, Bill McSweeney discusses the inadequacy of the scientific approach to security and criticizes the most recent attempts to surmount it. Drawing on contemporary trends in sociology, he develops a theory of the international order within which the idea of security takes on a broader range of meaning.